Agriculture media in India: March towards problem solving and professionalism - P. Chandra Shekara, (Journal of Agricultural Extension Management, 2025)
This qualitatively sums up, the present status of agriculture media in the country. Inadequate coverage i.e quantitative and lack of depth, i.e qualitative, handling of agriculture media by non-agriculture professionals and most importantly covering for the sake of covering without problem solving approach are the main impediments in strengthening agriculture media in the country